2005
DOI: 10.1007/s10397-005-0099-3
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic ovarian drilling (LOD) in patients with polycystic ovary syndrome (PCOS): an alternative approach to medical treatment?

Abstract: The operative treatment of polycystic ovary syndrome (PCOS) patients by laparoscopic ovarian drilling (LOD) is a widely used technique. However, the indication remains unclear. Excellent results with ovulatory cycles up to 9 years after surgery have been described. Nevertheless, pregnancy rates are not superior to a course of three to six treatment cycles with gonadotrophins in low-dose protocols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 71 publications
1
7
0
Order By: Relevance
“…Improvement in the endocrine data in our work is a remarkable observation are comparable with those previously reported showing a significant decrease in LH, testosterone, LH/FSH ratio 11,16,17 , significant increase of LH(p<0.001) few days post operatively in our study confirming report of the same phenomena by 16 , this finding is against those found in previous studies 9,18 showed no change in the level of LH and testosterone weeks and months after operation. Significant increase in SHBG in the current work confirmed by study 19 , furthermore another study demonstrated no change in this hormone 9 .The obtained result in the present study confirmed previous report 17,20 of significant reduction of FAI. Elevation of FSH is observed in the current and different studies 16,17 , secondary increase in FSH is controversial, studies reported no change 11,13,21 although one study done by Elgafor demonstrated reduced FSH in his results 22 this variability in the results may be due to different age groups, sample size and technique in their study.…”
Section: Discussionsupporting
confidence: 92%
“…Improvement in the endocrine data in our work is a remarkable observation are comparable with those previously reported showing a significant decrease in LH, testosterone, LH/FSH ratio 11,16,17 , significant increase of LH(p<0.001) few days post operatively in our study confirming report of the same phenomena by 16 , this finding is against those found in previous studies 9,18 showed no change in the level of LH and testosterone weeks and months after operation. Significant increase in SHBG in the current work confirmed by study 19 , furthermore another study demonstrated no change in this hormone 9 .The obtained result in the present study confirmed previous report 17,20 of significant reduction of FAI. Elevation of FSH is observed in the current and different studies 16,17 , secondary increase in FSH is controversial, studies reported no change 11,13,21 although one study done by Elgafor demonstrated reduced FSH in his results 22 this variability in the results may be due to different age groups, sample size and technique in their study.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, LOD has been evaluated as an alternative approach to the medical treatment of PCO-related anovulatory infertility, because it is not associated with risk of multiple pregnancy or ovarian hyperstimulation, and improves ovarian response to medical treatment (3). Nevertheless, two main drawbacks prevent LOD from being considered a primary approach to the treatment of POS: the risk inherent to any surgical procedure, and the risk of adhesion formation potentially interfering with fertility.…”
mentioning
confidence: 97%
“…On the basis of these data we have designed this large prospective study to investigate by means of a short-term second-look minilaparoscopy after LOD: [1] the incidence and site of postsurgical ovarian adhesion formation; [2] the correlation between the number of ovarian diathermy punctures and incidence and severity of adhesion; and [3] the side of the ovary treated as risk factor for adhesion formation.…”
mentioning
confidence: 99%
“…Similar results were observed in a study done by Thomas and Michaedl. 6 Study done by Poonam et al 7 showed pregnancy rate after 6 cycles of gonadotropins were 45.45% and it was 40% after the LOD group. The discrepancy with other studies could be due to many factors such as duration of infertility, follow-up period, and drugs used for induction of ovulation.…”
Section: Discussionmentioning
confidence: 97%